The Pull of Words: Reliving a Poetry Symposium through Found Poetry - Penwarden, Sarah; Schoone, Adrian (Art/Research International, 2021)
Poetic inquirers immerse themselves in the flow of life, listening for art in the ordinary world, offering a response through voice and written word. The biennial International Symposium on Poetic Inquiry, which draws poet-scholars from across disciplines and the world, showcases the artful use of poetry in research as a method of inquiry. In this article, the Fifth Symposium on Poetic Inquiry is relived by two attendees who interrogate found poems they each created from presentations and performances. The poems are brought together as a means of researching each author’s respective approaches to creating found poetry. In this article, the authors converse about their methodological frameworks: phenomenology and metaphor/ narrative. Central to this dialogue is how the found poem is listened for, and how artful responses are made to the pull of words. The authors conclude by considering the ethics of rehousing others’ words and the challenge this inquiry presents to our own private sense-making in academic conferences.